Grape Maturity and Wine Quality - Du Plessis, C. S.; Van Rooyen, P. C. (South African Journal of Enology and Viticulture, 2017)
Several indices calculated from grape juice analyses were submitted to statistical analyses in order to determine correlations of these indices with quality of wine made from grapes at different stages of maturity. Curvilinear relationships were obtained enabling an optimum point to be calculated relating grape maturity to maximum wine quality. The application of skin contact in the case of white wine cultivars resulted in earlier maxima for wine quality, thus compensating to an extent for earlier harvesting. The cultivars Chenin blanc, Colombar, Pinotage and Cabernet Sauvignon were examined as outlined above over several years.